Gambaran Pengetahuan dan Sikap Ibu Tentang Pemberian Imunisasi Dasar Lengkap Pada Balita di Desa Bangilan Wilayah Kerja Puskesmas Bangilan - Kuswaningsih, Kuswaningsih; Yunariyah, Binti; Jannah, Roudlotul (Peneliti.net, 2024)
Immunization is an effort to actively increase a person's immunity against a disease so that when exposed to the disease they will not get sick or only experience mild illness. In Indonesia the coverage of immunization has decreased, name there are 1.7 million babies who have not received basic immunization with a coverage of only 84% during the 2019-2021 period. The purpose of this study was to describe the knowledge and attitudes of mothers about giving complete basic immunization to toddlers in the village of Bangilan, the working area of the Bangilan Health Center. Descriptive research design with a cross-sectional approach. The study population was mothers who had toddlers in Bangilan village, totaling 89 people, with a sample size of 72 people. The sampling technique used is purposive sampling. The research variable is the mother's knowledge and attitude about giving complete basic immunization to toddlers. How to collect data with a questionnaire. The results showed that the majority of mothers who had toddlers had sufficient knowledge about giving complete basic immunization with a total of 49 respondents (68%) and that almost all mothers had a negative attitude about giving complete basic immunization to toddlers with a total of 58 respondents (81%). It is hoped that the Puskesmas can conduct counseling about giving complete basic immunization regarding the benefits, objectives, side effects and impacts of not being immunized on toddlers in Bangilan village to increase the knowledge and attitude of mothers so that no mother thinks that complete basic immunization for toddlers is not important.